Family and Politics to Related Party Transaction in Indonesia’s Mining Companies: Does Corporate Governance Matter? - Fatchan, Fuad; Potina Histika Pawitra Mahandani; Ilham Nuryana Fatchan; Fatchan Achyani (Riset Akuntansi dan Keuangan Indonesia, 2023)
This study discusses the influence of family ownership and political connections on related party transactions with corporate governance variables as a moderating variable in mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses audit quality, firm age, profitability and firm size as control variables. This type of research is quantitative research. The data used is secondary data using purposive sampling. This study uses the Eviews test tool and uses the random effect model and Moderated Regression Analysis (MRA). The results of the study show that family ownership and political connections have an effect on related party transactions. Furthermore, corporate governance weakens the influence of family ownership and political connections on related party transactions.